XP endo® file: An update review - Harakh Chand Baranwal; Nidhi Singh; Amrita Kumari (Wolters Kluwer Medknow Publications, 2020)
Clinical research has still focus on three-dimensional (3D) cleaning, shaping, and obturation of the oval root canal by improving irrigation, creating new alloys for instruments, and creating new sealers. This article only deals the MaxWire® technology instruments XP Endo® Shaper, Finisher, and XP Endo® Retreatment file and analyzes how they are effective in 3D cleaning and shaping, in biofilm removal, triple antibiotic paste removal, and also for debris and smear layer removal.